Comparison of the Effectiveness of Flipped Classroom and Conventional Learning Models on Mathematics Comprehension of Grade V Students: Perbandingan Efektivitas Model Pembelajaran Flipped Classroom dan Konvensional pada Pemahaman Matematika Siswa Kelas V - Chusna, Puji Asmaul; Purwandari, Wahyu (Madrosatuna: Journal of Islamic Elementary School, 2025)
This study examines the comparison of the effectiveness of the flipped classroom learning model and the conventional model on the mathematics understanding of fifth-grade elementary school students.Using a quasi-experimental design involving 40 students divided into experimental and control groups, the research was conducted over 8 weeks with a focus on fractions, flat shapes, and data processing.The research results show that the flipped classroom model is significantly more effective in improving students' mathematical understanding (N-gain 0.68) compared to the conventional model (N-gain 0.42) with an effect size of 0.76.In-depth analysis reveals that the flipped classroom has the strongest impact on aspects of conceptual and applicative understanding, while the most influential factors for its success are the quality and accessibility of learning videos, student engagement in class activities, and parental support.These findings provide empirical evidence that the integration of technology through the flipped classroom model can be an innovative solution to improve the quality of mathematics learning in elementary schools, although its implementation needs to consider technological infrastructure, teacher readiness, and learning environment support.